Rate of Adsorption of Laccaic Acid on Silk Fiber - Kongkachuichay, Paisan; Chinvongamon, Nontalee; Chitangkoon, Arunsiri (Engineering and Applied Science Research, 2013)
The effect of temperatures on the rate of adsorption of laccaic acid on silk fiber was investigated. After degummed, silk fiber, the hybrid race, was dyed with lac dye (laccaic acid) which erythrolaccin had been removed first. The dyeing temperatures were set at 28º 60º and 80º C. The amount of adsorbed dye on fiber was measured by UV-vis spectrophotometer. The results showed that the rate of adsorption of laccaic acid on silk fiber increased when dyeing temperatures were increased. The time required to reach the maximum adsorption was decreased from 5,760 min 180 min and 90 min respectively. The maximum adsorption occurred at 12.271 mg/g silk, 4.756 mg/g silk and 0.496 mg/g silk, respectively. Finally, the apparent diffusion coefficient was found to be increased from 3.10 x 10-10 cm2/sec to 10.051 x 10-9 cm2/sec and 11.938 x 10-9 cm2/sec.